Evaluation of Teachers' Technological Pedagogical Content Knowledge (TPACK) Understanding Profile - Ratnaya, I Gede; Hunaepi, Hunaepi; Wardani, Ketut Sri Kusuma; Sukiastini, Sukiastini (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This research aimed to assess teachers' understanding of the Technological Pedagogical Content Knowledge (TPACK) structure and investigate whether TPACK components differ based on gender characteristics. The research method used was a cross-sectional survey, a quantitative approach aimed at examining a condition at a specific point in time and exploring relationships between variables. Respondents were randomly selected from 102 teachers spread across Lombok Island, comprising 48 female teachers and 56 male teachers. The research instrument utilized a TPACK questionnaire measuring CK, PK, TK, TPTCK, and TPCK, adapted from Liang et al., 2013. The analysis results indicated that teachers demonstrated a solid understanding of Content Knowledge (CK) and Pedagogical Knowledge (PK), signifying a strong grasp of the taught material and effective teaching techniques. However, concerning Pedagogical Content Knowledge (PCK), their understanding of how to teach specific content required further attention. Nevertheless, they exhibited a robust understanding of Technological Knowledge (TK), Technological Pedagogical Content Knowledge (TPTCK), and Pedagogical Content Knowledge (TPCK), although the level of understanding in TPCK was slightly higher than TPTCK. Meanwhile, the gender-based analysis showed significant differences in TPACK understanding between the genders in the TK, TPTCK, and TPCK components, but no significant differences were observed in the PK, CK, and PCK components. This highlights the importance of understanding gender differences related to specific aspects of technology, education, and content knowledge. Further research or in-depth analysis is needed to comprehend the underlying factors causing these differences and their implications within the educational context and curriculum development.